BRIDGE THE GAP IN WORKPLACE RELATIONSHIPS. Issue 104 (14th January 2022) - Edwards, Jennifer; McCleary, Katie
Abstract: The authors "explore a foundational skill and tool in our curriculum: the ability to "show up clean" using psychological flexibility and distance, along with the power of naming a negative "Inner Narrator" who threatens relationships." They note that many people feel disconnected in the workplace, a problem that threatens crucial working relationships. They state that "research shows that people don't quit because of pay, but rather because of how they are treated by the people they work alongside." They reference a 2015 Virgin Pulse survey, which found that "nearly 40% of people said that their co‐workers were the top reason that they loved working for a particular company, and 66% of those relationships positively impact their focus and productivity." The article draws on an example of one particular executive, , Francisco, to illustrate key points. Describing the work of the authors' firm, they "equip working professionals with tangible skills on how to show up clean and curious so that they can work effectively with a diverse spectrum of people. Our framework offers easy‐to‐use and memorable tools that help people increase their self‐awareness by understanding how their biology, psychology, lived experiences, default behaviors, and communication styles intersect and impact their relationships and conversations."